2019
DOI: 10.1093/gbe/evz199
|View full text |Cite
|
Sign up to set email alerts
|

New Non-Bilaterian Transcriptomes Provide Novel Insights into the Evolution of Coral Skeletomes

Abstract: A general trend observed in animal skeletomes—the proteins occluded in animal skeletons—is the copresence of taxonomically widespread and lineage-specific proteins that actively regulate the biomineralization process. Among cnidarians, the skeletomes of scleractinian corals have been shown to follow this trend. However, distributions and phylogenetic analyses of biomineralization-related genes are often based on only a few species, with other anthozoan calcifiers such as octocorals (soft corals), not being ful… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 78 publications
(108 reference statements)
0
28
0
Order By: Relevance
“…Nevertheless, the fact that only T. musica 's octo-galaxin 1 possess the endoprotease target motif characteristic of scleractinian skeletogenic galaxins (Fukuda et al 2003) , and that the observed polyphyly within galaxin phylogenies are likely affected by the inclusion of false homologs, sensitivity to analytical parameters, and aligning algorithms (Conci et al 2019) makes difficult to rule out the hypothesis of an ancient, biomineralization-related recruitment of (octo)galaxins prior to the divergence of octocorals from the remaining Anthozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the fact that only T. musica 's octo-galaxin 1 possess the endoprotease target motif characteristic of scleractinian skeletogenic galaxins (Fukuda et al 2003) , and that the observed polyphyly within galaxin phylogenies are likely affected by the inclusion of false homologs, sensitivity to analytical parameters, and aligning algorithms (Conci et al 2019) makes difficult to rule out the hypothesis of an ancient, biomineralization-related recruitment of (octo)galaxins prior to the divergence of octocorals from the remaining Anthozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Common contaminants, potential symbiont, and bacterial sequences were filtered. Peptides were mapped against respective octocoral ( Conci et al. 2019) and M. digitata ( González-Pech et al.…”
Section: Methodsmentioning
confidence: 99%
“…According to an analysis of SOM homologs in cnidarians, including Hydrozoa, several proteins related to biomineralization were identified [38]. Extracellular adhesion proteins and carbonic anhydrases homologs were the most common proteins found (e.g., in Millepora alcicornis, Millepora complanata, and Millepora squarrosa).…”
Section: Skeletogenesis and Oamentioning
confidence: 99%
“…Homolog proteins include enzymes such as peptidase-1 and peptidase-2 as well as acidic proteins like SAARP-1, SAARP-2, acidic SOMP, CARP4, CARP5, Integrin-like and two SAARP-like proteins; those proteins are involved in calcite formation [39]. Two galaxin ortholog proteins (Galaxin and Galaxin-2) [38] have been fully characterized by the calcifying matrix of scleractinian corals [40]. More interestingly, carbonic anhydrases, which are known to precipitate CaCO 3 in different calcareous organisms [41], have been identified in Hydrozoa species, CruCA-4, and Putative CA [38].…”
Section: Skeletogenesis and Oamentioning
confidence: 99%
See 1 more Smart Citation